Cerambycidae (Coleoptera) types of the Fernando de Zayas collection, Havana, Cuba - Nearns, Eugenio H.; Branham, Marc A.; Bybee, Seth M. (Zootaxa, 2006)
Habitus photographs of the cerambycid types (Coleoptera: Cerambycidae) of the Fernando de Zayas Collection, Havana, Cuba, are presented. Color photographs are available on the Internet. Lectotypes are herein designated for two taxa, Plectromerus pinicola Zayas and Phidola superba Zayas (= Eupogonius superbus (Zayas)).